Answers

2015-07-18T13:53:12+05:30
3x-2x = -8+1
x=-7
value of x is -7
0
2015-07-18T18:36:45+05:30
|3x-1|=|2x-8|\\ \\ \Rightarrow \pm(3x-1)= \pm (2x-8)

There are total 4 cases possible:

Case-1:
+(3x - 1) = +(2x - 8) 
⇒ 3x - 1 = 2x - 8
⇒ 3x - 2x = -8 + 1
⇒ x = -7

Case-2:
+(3x - 1) = -(2x - 8) 
⇒ 3x - 1 = -2x + 8
⇒ 3x + 2x = 8 + 1
⇒ 5x = 9
⇒ x = 9/5

Case-3:
-(3x - 1) = +(2x - 8) 
⇒ +(3x - 1) = -2(x - 8)
It is same as case-2. So x = 9/5

Case-4:
-(3x - 1) = -(2x - 8) 
⇒ +(3x - 1) = +(2x - 8)
It is same as case-1. So x = -7.

So x = -7 and +9/5.
0